2022
DOI: 10.26434/chemrxiv-2022-kxkt3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In-Liquid Plasma Modified Nickel Foam: NiOOH/NiFeOOH Active Site Multiplication for Electrocatalytic Alcohol, Aldehyde, and Water Oxidation

Abstract: The oxygen evolution reaction (OER) and the value-added selective oxidation of renewable organic substrates are the most promising reactions to supply electrons and protons for the synthesis of sustainable fuels. To meet industrial requirements, new methods for a simple, fast, environmentally friendly, and cheap synthesis of robust, self-supported, high surface area electrodes are required. Herein, we report on a novel in liquid plasma electrolysis approach for the growth of hierarchical nanostructures on nick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Nevertheless, some reports have shown that the detour of in-situ OER interlayer species exchange by carbonate or alkaline hydroxide can be beneficial for the catalytic activity, and as such in-situ formed catalysts have been demonstrated to be more active than the same directly synthesized carbonate intercalated materials. [59,60,63,64,[68][69][70][71] This is especially the case for large intercalated species that strongly increase the d-spacing like dodecylsulfate (d-spacing > 20 Å), [64,65,69] Intercalated species (Pre)catalyst phase [a] and reference Comments Acetaldehyde C 2 H 4 O CoFe-LDH [81] Alkoxides C n H m O À NiFe LDH, [82] CoFe-LDH, [81] NiEt 2 , [26] Co(Fe)OHMe [27] Alkoxides likely oxidize under OER conditions, [83] alkoxide can replace the OH groups of LDH [26,27] Benzoate C 7 H 5 O 2 À Co-LDH, [68,73] Ni-LDH [72] d-spacing…”
Section: The Effect Of Intercalated (Oxy)anions On the Oermentioning
confidence: 99%
“…Nevertheless, some reports have shown that the detour of in-situ OER interlayer species exchange by carbonate or alkaline hydroxide can be beneficial for the catalytic activity, and as such in-situ formed catalysts have been demonstrated to be more active than the same directly synthesized carbonate intercalated materials. [59,60,63,64,[68][69][70][71] This is especially the case for large intercalated species that strongly increase the d-spacing like dodecylsulfate (d-spacing > 20 Å), [64,65,69] Intercalated species (Pre)catalyst phase [a] and reference Comments Acetaldehyde C 2 H 4 O CoFe-LDH [81] Alkoxides C n H m O À NiFe LDH, [82] CoFe-LDH, [81] NiEt 2 , [26] Co(Fe)OHMe [27] Alkoxides likely oxidize under OER conditions, [83] alkoxide can replace the OH groups of LDH [26,27] Benzoate C 7 H 5 O 2 À Co-LDH, [68,73] Ni-LDH [72] d-spacing…”
Section: The Effect Of Intercalated (Oxy)anions On the Oermentioning
confidence: 99%
“…16 The literature has highlighted that Ni-, and Co-containing LDHs, as the electrocatalysts, can notably augment the electrochemical performance of the BOR. 17,18 Evidence from prior research indicates that the higher oxidation states of Co or Ni species, observable only at elevated oxidation potentials, serve as the active sites for such electrochemical organic oxidations, including the BOR. [19][20][21] A careful approach to catalyst design, complemented by the fine-tuning of both the active catalytic sites and the electron transfer mechanism, is imperative.…”
Section: Introductionmentioning
confidence: 99%